The Correlation between Early Stages of Life Exposed to Chinese Famine and Cognitive Decline in Adulthood: Nutrition of Adulthood Plays an Important Role in the Link? - Rong, Hongguo; Xi, Yuandi; An, Yu; Tao, Lingwei; Zhang, Xiaona; Yu, Huiyan; Wang, Ying; Qin, Zhongsheng; Xiao, Rong (Frontiers in Aging Neuroscience, 2018)
Objective: The aim of this study was to investigate whether people exposed to the Chinese Famine in fetal period or in multiple stages of childhood are associated with cognitive decline in adulthood. Furthermore, the nutritional environment of adulthood was explored as an important factor in this correlation. Methods: 1162 adults born between 1952 and 1964 were recruited. They were divided into 5 groups which were non-exposed group, fetal-exposed group, early childhood-exposed group, mid childhood-exposed group and late childhood-exposed group. Cognitive function was measured by using a comprehensive neuropsychological battery test, including Montreal cognitive assessment-Beijing version, mini-mental state examination, auditory verbal learning test, digit span forward, digit span backward, trail making test, and digit symbol test. Semi-quantified food frequency questionnaire (FFQ) was used to assess the dietary nutrition in their adulthood. The dietary nutrient consumption pattern was identified by Two-step and K-means cluster analysis. Results: The significant differences in cognitive function were manifested in different groups. Compared with non-exposed group, subjects in fetal-exposed group had a higher risk of mild cognitive impairment (MCI) (OR 1.51 95% CI 1.02-2.23, P = 0.039) and global cognitive decline (OR 1.68 59% CI 1.02-2.77, P = 0.044). The similar result was also observed in subjects of early childhood-exposed group. Otherwise, subjects who were classified in high nutrient consumption pattern had higher risk of cognitive decline. Moreover, the higher consumption of several nutrients such as fat, carbohydrate and manganese were associated with worse performance on digit span forward, digit span backward, trail making test A, trail making test B and digit symbol. Conclusion: Early stages of life exposed to the Chinese Famine were associated with higher risk of cognitive decline in adulthood. The stronger associations were manifested in the people with high nutrient consumption pattern. The consumption of fat, carbohydrate and manganese were associated with multiple domains cognitive decline.